A Raman spectro-microscopic investigation of ETFE-based radiation-grafted anion-exchange membranes. Issue 75 (11th October 2017) - Lee, Wai Hin; Crean, Carol; Varcoe, John R.; Bance-Soualhi, Rachida
Abstract : Raman spectro-microscopy on a radiation-grafted anion-exchange membrane detected alkali degradation throughout its cross-section that quantitatively matched loss of ion-exchange capacity. Abstract : This study used Raman spectro-microscopy to investigate the synthesis and degradation of radiation-grafted anion-exchange membranes (RG-AEM) made using 50 μm thick poly(ethylene-co-tetrafluoroethylene) (ETFE) films, vinylbenzyl chloride (VBC) monomer, and 1-methylpyrrolidine (MPY) amination agent. The data obtained confirmed the operation of the grafting-front mechanism. VBC grafting times of 1 and 4 h led to low degrees of grafting homogeneity, while 72 h led to extreme levels of grafting that resulted in mechanically weak RG-AEMs due to the excessive H2 O contents. A grafting time of 16 h was optimal yielding a RG-AEM with an ion-exchange capacity (IEC) of 2.06 ± 0.02 mmol g −1 ( n = 3). An excess of grafting was detected at the surface of this RG-AEM (at least within the first few μm of the surface). This RG-AEM was then degraded in O2 -purged aqueous KOH (1.0 mol dm −3 ) for 14 d at 80 °C. Degradation was detected throughout the RG-AEM cross-section, where the Raman data was quantitatively consistent with the loss of IEC. A slight excess of degradation was detected at the surface of the RG-AEM. Degradation involved the loss of whole benzyl-1-methypyrrolidinium grafted units as well as the direct attack on the pendent (cationic) pyrrolidinium groups by the hydroxide anions.